2017
DOI: 10.1038/onc.2017.52
|View full text |Cite
|
Sign up to set email alerts
|

Selected mitochondrial DNA landscapes activate the SIRT3 axis of the UPRmt to promote metastasis

Abstract: By causing mitochondrial DNA (mtDNA) mutations and oxidation of mitochondrial proteins, reactive oxygen species (ROS) leads to perturbations in mitochondrial proteostasis. Several studies have linked mtDNA mutations to metastasis of cancer cells but the nature of the mtDNA species involved remains unclear. Our data suggests that no common mtDNA mutation identifies metastatic cells; rather the metastatic potential of several ROS-generating mutations is largely determined by their mtDNA genomic landscapes, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
71
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 54 publications
(136 reference statements)
11
71
0
Order By: Relevance
“…The authors attributed the variability to levels of mtDNA heteroplasmy, most notably in the MDA-MB-157 human breast carcinoma cell line. However, on average the invasive cell lines had an increase in a shift toward a more glycolytic phenotype [73]. Other papers report the ratio of oxidative phosphorylation to glycolysis to either increase [74] or decrease [75] as invasion and metastasis increases.…”
Section: Mitochondrial Dna and Metastasismentioning
confidence: 99%
See 2 more Smart Citations
“…The authors attributed the variability to levels of mtDNA heteroplasmy, most notably in the MDA-MB-157 human breast carcinoma cell line. However, on average the invasive cell lines had an increase in a shift toward a more glycolytic phenotype [73]. Other papers report the ratio of oxidative phosphorylation to glycolysis to either increase [74] or decrease [75] as invasion and metastasis increases.…”
Section: Mitochondrial Dna and Metastasismentioning
confidence: 99%
“…Taking this into consideration Kenny et al . analyzed the role of the mitochondrial unfolded protein response (UPR MT ) [73] and found that activation of SOD2 through a SIRT3/FOXO3a/SOD2 axis downstream of the UPR MT may increase mitochondrial biogenesis and the antioxidant response in aggressive disease. Furthermore, the authors demonstrated that SOD2 expression is an important component in the regulation of the invasion, but is not sufficient to drive the invasive phenotype.…”
Section: What Are the Signals?mentioning
confidence: 99%
See 1 more Smart Citation
“…Kenny and colleagues discovered that the activation of SIRT/FOXO/SOD2 axis of the mitochondrial unfolded protein response (UPR mt ) is a common feature of the mtDNA of metastatic cells (25). In particular, super-oxide dismutase 2 (SOD2) was found to be substantially increased in more highly metastatic human breast cancer cell lines (MDA-MB-231, MDA-MB-361, and MDA-MB-157) compared with less metastatic cell lines MCF-7 and ZR-75-1.…”
Section: Mtdna and Metastasismentioning
confidence: 99%
“…In particular, super-oxide dismutase 2 (SOD2) was found to be substantially increased in more highly metastatic human breast cancer cell lines (MDA-MB-231, MDA-MB-361, and MDA-MB-157) compared with less metastatic cell lines MCF-7 and ZR-75-1. Interestingly, Kenny and colleagues found that there was no one specific mtDNA mutation that drove metastasis in the cancer cells, but rather the composition of the mtDNA genome [i.e., presence or absence of reactive oxygen species (ROS); activation of the SIRT/FOXO/SOD2 axis of the UPR mt ] dictated either promotion or repression of cancer cell metastasis (25). In comparison with Kenny and colleagues, Arnold and colleagues sequenced the mitochondrial genome of 10 prostate cancer patients with bone metastases (26).…”
Section: Mtdna and Metastasismentioning
confidence: 99%